2019
DOI: 10.1016/j.cimid.2018.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Brucella canis induces canine CD4+ T cells multi-cytokine Th1/Th17 production via dendritic cell activation

Abstract: Brucella canis is a small intracellular Gram-negative bacterium that frequently leads to chronic infections highly resistant to antibiotic therapy in dogs. Also, it causes mild human brucellosis compared to other zoonotic Brucella spp. Herein we characterize the cellular immune response elicited by B. canis by analysing human and canine CD4+ T cells after stimulation with autologous monocyte-derived dendritic cells (MoDCs). Human and canine B. canis-primed MoDCs stimulated autologous CD4+ T cells; however, a T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
4
0
2
Order By: Relevance
“…These authors demonstrated that B. canis induces the expression of costimulatory molecules on both canine and human dendritic cells, but while infected human dendritic cells demonstrate TH1-skewed proinflammatory cytokine production, the canine cells show a mixed TH1-TH17 response (Pujol et al, 2017). This effect was also observed in CD4+ T lymphocytes stimulated by dendritic cells previously infected with B. canis (Pujol et al, 2019). These findings demonstrate that host specificity can play an important role in the immune response to Brucella spp.…”
Section: Interaction With Natural Host Cellsmentioning
confidence: 93%
See 1 more Smart Citation
“…These authors demonstrated that B. canis induces the expression of costimulatory molecules on both canine and human dendritic cells, but while infected human dendritic cells demonstrate TH1-skewed proinflammatory cytokine production, the canine cells show a mixed TH1-TH17 response (Pujol et al, 2017). This effect was also observed in CD4+ T lymphocytes stimulated by dendritic cells previously infected with B. canis (Pujol et al, 2019). These findings demonstrate that host specificity can play an important role in the immune response to Brucella spp.…”
Section: Interaction With Natural Host Cellsmentioning
confidence: 93%
“…TH17 lymphocytes are also associated with autoimmune disorders and auto-antibody formation (Cornelius and Lamarca, 2014). The TH17 component of the response in canine dendritic cells, as suggested by Pujol et al (2017), may reflect an increased susceptibility in this host and/or help to explain the incidence of osteoarticular lesions, particularly diskospondylitis, as well as antibody-mediated destruction of sperm in infected dogs (George and Carmichael, 1984;Pujol et al, 2019). Antibody-mediated attack on sperm is also a prominent feature of B. ovis infection in rams and the possible role of IL-17 remains to be explored in this species (Paolicchi et al, 2000).…”
Section: Interaction With Natural Host Cellsmentioning
confidence: 99%
“…In addition, the expression of the "role of macrophages, fibroblast, and endothelial cells in rheumatoid arthritis, " "role of osteoblasts, osteoclasts, and chondrocytes in rheumatoid arthritis, " and the "neuroinflammation signaling pathway" associated with arthritis and neurological symptoms caused by the known Brucella species has been also observed (24,(30)(31)(32)(33).…”
Section: Points This Finding Is Observed Because the Expression Of Twomentioning
confidence: 99%
“…Es muy probable que la infección por B. canis en los seres humanos se encuentre subdiagnosticada debido a la sintomatología inespecífica (3,4,13), y a que la bacteria no se puede identificar mediante las pruebas serológicas empleadas de rutina para el diagnóstico de otras especies del género (13). Aunque todavía se consideran poco frecuentes, un número creciente de estudios en la última década ha documentado infecciones con B. canis como causa de endocarditis, peritonitis y otros cuadros clínicos (4).…”
Section: Colombiaunclassified
“…La bacteria Brucella canis es considerada el principal agente causal de la brucelosis canina (1)(2)(3), aunque otras especies del género, como B. abortus, B. suis y B. melitensis, pueden infectar de forma transitoria a los perros (4). El cuadro clínico en el perro es variable y se encuentran desde casos asintomáticos (1,5,6), hasta abortos, orquitis, epididimitis, prostatitis (2,7), discoespondilitis (8), endoftalmitis (9) o linfadenomegalia (10).…”
unclassified